Sharing the burden: on the division of parental care and vocalizations during incubation. (12th April 2019) - Kavelaars, Marwa M; Lens, Luc; Müller, Wendt
Abstract : In biparental species, both pair-members contribute to parental care to enhance offspring growth and survival. The cost of care should be equally distributed between them. Parents are therefore expected to adjust their parental investment to their partner's contribution. We found that lesser black-backed gull pairs that vocalized more divided their incubation stints more equally. Furthermore, pairs that shared incubation more equally raised offspring of higher quality when experiencing more challenging conditions. Abstract: In species with biparental care, individuals only have to pay the costs for their own parental investment, whereas the contribution of their partner comes for free. Each parent hence benefits if its partner works harder, creating an evolutionary conflict of interest. How parents resolve this conflict and how they achieve the optimal division of parental tasks often remains elusive. In this study, we investigated whether lesser black-backed gulls ( Larus fuscus ) divide parental care during incubation equally and whether this correlates with the extent of vocalizations between pair-members during incubation. We then investigated whether pairs showing more evenly distributed incubation behavior had a higher reproductive success. To this end, we recorded incubation behavior and vocalizations for 24-h time periods. Subsequently, we experimentally increased or decreased brood sizes in order to manipulate parental effort, and followed offspring development from hatching till fledging. Although incubation bouts were, on average, slightly longer in females, patterns varied strongly between pairs, ranging from primarily female incubation over equal sex contributions to male-biased incubation. Pairs contributing more equally to incubation vocalized more during nest relief and had a higher reproductive output when brood sizes were experimentally increased. Thus, vocalizations and a more equal division of parental care during incubation may facilitate higher levels of care during the nestling period, as suggested by a greater reproductive success when facing high brood demand, or they indicate pair quality.